Benefits of rescreening newborns of mothers affected by autoimmune hypothyroidism. Issue 5 (5th August 2022) - Cavarzere, Paolo; Palma, Laura; Nicolussi Principe, Lara; Vincenzi, Monica; Lauriola, Silvana; Gaudino, Rossella; Murri, Virginia; Lubrano, Luigi; Rossi, Giuliana; Sallemi, Alessia; Fattori, Ermanna; Camilot, Marta; et al.
Abstract : Introduction: Infants of mothers with autoimmune hypothyroidism (AH) are at risk of developing late-onset hypothyroidism, often escaping at newborn screening. This condition might be caused both by the action of maternal antibodies and/or by maternal treatment. Objectives: The aim of this study is to evaluate the prevalence of AH in the mothers of children born in Veneto region, Italy, and to define what is the most appropriate management for these newborns. Methods: Newborns of six different hospitals with a mother suffering from AH and with negative neonatal screening for congenital hypothyroidism (CH) were included in the study. Between 15 and 20 days of life, we collected a serum sample for the evaluation of thyroid function (thyroid-stimulating hormone (TSH), free thyroxine (FT4), free triiodothyronine (FT3)) and anti-thyroid antibodies. On the same occasion, a capillary blood sampling was performed for a second screening test. Results: Maternal AH has a prevalence of 3.5%. A total of 291 newborns were enrolled from November 2019 to May 2021. Whereas the 11.4% of infants had a slight elevated serum TSH (>6 mU/L) and required a follow-up, only 2 children presented an elevated TSH level at the second screening test. One of these, with the gland in situ, showed persistently elevated serum TSH levels and required treatment with levothyroxine. Conclusions: Maternal AH rarely caused neonatal thyroid dysfunction. We suggest to reassess newborns from mothers with AH 15 days after birth by means of a second neonatal screening test. This procedure avoids false negatives due to maternal thyroid status, is less invasive and cheaper than the serum TSH evaluation, and prevents a long follow-up.